SISTEM KONTROL DAN MONITORING PH SERTA PEMBERIAN PAKAN IKAN OTOMATIS PADA AQUAPONIK BERBASIS MIKROKONTROLLER - Teguh Dwiky Putra; Ratna Aisuwarya (Universitas Andalas, 2022)
The research was purposed to create an aquaponic cultivation system that can monitor and control the pH value and provide automatic fish feed based on time scheduling, and detect the amount of fish feed. Then the results of monitoring pH and the amount of fish feed in the feed will be displayed on the smartphone via the Telegram application. The components used in this system consist of NodeMCU, pH-4502C sensor, ultrasonic sensor, DC pump, servo motor, RTC, wiper pump. Aquaponic cultivation systems can be described as a combination of aquaculture (fish farming) and hydroponics (plant/vegetable cultivation without soil media). In addition to fish farming, fish feeding is generally done by humans manually. This has several drawbacks, namely the frequent feeding of fish that is not in accordance with the schedule and the amount of feed given is not measured. As a result of this, it can be in the form of lack of fish nutrition, stunted fish growth, illness, even causing fish death so that fish yields are not optimal. From the research conducted, the results obtained are the percentage of success in the process of monitoring and controlling the pH of the water according to the scheduled time with an accuracy of pH readings of 98.79% and an accuracy of controlling pH of 100%. The percentage accuracy of the amount of feed given is 99.201%. The percentage of accuracy of detecting feed volume is 60.348%.